GUIDANCE AND COUNSELING SERVICES STRATEGY IN INCREASING STUDENT CONFIDENCE - Annisyah, Fitry; Fitri Syakinah, Tengku Ananda; Lesmana, Gusman (BRIGHT VISION Journal of Language and Education, 2023)
This research aims to elaborate on the theoretical basis and strategies for guidance and counseling services to increase self-confidence. The research method used is the library research method which is carried out using literature in the form of books, notes or other literature as the main object. The results of this research are the elaboration of the theoretical basis and strategies for guidance and counseling services to increase overall self-confidence including: 1) understanding self-confidence, 2) characteristics of self-confidence, 3) factors that influence self-confidence, 4) components of guidance and counseling services, 5) strategies for guidance and counseling services to increase self-confidence.